2022
DOI: 10.1039/d2nj00416j
|View full text |Cite
|
Sign up to set email alerts
|

Pore engineering of biomolecule-based metal–organic framework nanocarriers for improving loading and release of paclitaxel

Abstract: Metal–organic frameworks (MOFs) incorporated with biomolecules, known as b-MOFs, have shown interest in biomedical applications. However, it is difficult and challenging to synthesize these materials at the nanoparticle size because...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Beyond the proof-of-concept demonstrations in this work, the optical set-up described here should be amenable to other solid-state REE sensing materials as well; future innovations in the development of REE sensors will further improve the sensitivity and selectivity of the probe. Notably, other synthetic innovations, such as decreases in the size of the MOF sensing material, 47 should also improve performance by providing a higher quality film coating on the optical fiber. Alternative optical configurations may be envisioned that could further reduce the size of the sensing platform; for example, a shorter bifurcated fiber optic cable could be used, or the bifurcated cable could be replaced entirely using a beam splitter.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the proof-of-concept demonstrations in this work, the optical set-up described here should be amenable to other solid-state REE sensing materials as well; future innovations in the development of REE sensors will further improve the sensitivity and selectivity of the probe. Notably, other synthetic innovations, such as decreases in the size of the MOF sensing material, 47 should also improve performance by providing a higher quality film coating on the optical fiber. Alternative optical configurations may be envisioned that could further reduce the size of the sensing platform; for example, a shorter bifurcated fiber optic cable could be used, or the bifurcated cable could be replaced entirely using a beam splitter.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome the size limitation, mesoporous MOFs such as Zn-BPDC and Zn-azoBPDC, 29 and the Fe-TCPP PCN-600, 30 have been studied. However, despite these recent advances in MOF-based PTX formulations, direct evidence of PTX pore loading remains elusive and more importantly, a deficient therapeutic effect prevails as compared with the free-administered drug.…”
Section: Introductionmentioning
confidence: 99%
“…The enhanced biocompatibility of the b-MOF owing to the integration of biomolecules into the structure compensates for the hydrophobic nature of PTX, enabling secure drug delivery to the cancer site. Although several biomolecule-incorporated MOFs have demonstrated effectiveness in biomedical applications, [37,38] the microwave-assisted synthesis of such materials in the nanoscale (∼ 200 nm) has not been reported. In addition, by employing the MW method, this novel strategy yields homogenous particles with an average diameter of 200 nm, optimizing the permeability and retention effect for enhanced drug accumulation at the tumor site.…”
Section: Introductionmentioning
confidence: 99%
“…[37] Various researchers have reported on the potential of these materials as nanocarriers. [38] Although these materials exhibit exceptional drug loading and release capabilities, their microscale crystal structures preclude their application as nanocarriers and drug delivery agents. Notably, no study has demonstrated a method to synthesize these materials at the nanoscale.…”
Section: Introductionmentioning
confidence: 99%